The prognostic significance of weight loss in chronic obstructive pulmonary disease‐related cachexia: a prospective cohort study. Issue 6 (17th June 2019) - Kwan, Hoi Yee; Maddocks, Matthew; Nolan, Claire M.; Jones, Sarah E.; Patel, Suhani; Barker, Ruth E.; Kon, Samantha S.C.; Polkey, Michael I.; Cullinan, Paul; Man, William D.‐C.
Abstract: Background: Cachexia is an important extra‐pulmonary manifestation of chronic obstructive pulmonary disease (COPD) presenting as unintentional weight loss and altered body composition. Previous studies have focused on the relative importance of body composition compared with body mass rather than the relative importance of dynamic compared with static measures. We aimed to determine the prevalence of cachexia and pre‐cachexia phenotypes in COPD and examine the associations between cachexia and its component features with all‐cause mortality. Methods: We enrolled 1755 consecutive outpatients with stable COPD from two London centres between 2012 and 2017, stratified according to European Respiratory Society Task Force defined cachexia [unintentional weight loss >5% and low fat‐free mass index (FFMI)], pre‐cachexia (weight loss >5% but preserved FFMI), or no cachexia. The primary outcome was all‐cause mortality. We calculated hazard ratios (HRs) using Cox proportional hazards regression for cachexia classifications (cachexia, pre‐cachexia, and no cachexia) and component features (weight loss and FFMI) and mortality, adjusting for age, sex, body mass index, and disease‐specific prognostic markers. Results: The prevalence of cachexia was 4.6% [95% confidence interval (CI): 3.6–5.6] and pre‐cachexia 1.6% (95% CI: 1.0–2.2). Prevalence was similar across sexes but increased with worsening Global Initiative for Chronic Obstructive Pulmonary Disease spirometric stage and Medical Research Council dyspnoea score (all P < 0.001). There were 313 (17.8%) deaths over a median (interquartile range) follow‐up duration 1089 (547–1704) days. Both cachexia [HR 1.98 (95% CI: 1.31–2.99), P = 0.002] and pre‐cachexia [HR 2.79 (95% CI: 1.48–5.29), P = 0.001] were associated with increased mortality. In multivariable analysis, the unintentional weight loss feature of cachexia was independently associated with mortality [HR 2.16 (95% CI: 1.31–3.08), P < 0.001], whereas low FFMI was not [HR 0.88 (95% CI: 0.64–1.20), P = 0.402]. Sensitivity analyses using body mass index‐specific, age‐specific, and gender‐specific low FFMI values found consistent findings. Conclusions: Despite the low prevalence of cachexia and pre‐cachexia, both confer increased mortality risk in COPD, driven by the unintentional weight loss component. Our data suggest that low FFMI without concurrent weight loss may not confer the poor prognosis as previously reported for this group. Weight loss should be regularly monitored in practice and may represent an important target in COPD management. We propose the incorporation of weight monitoring into national and international COPD guidance.